Do Androids dream of electric sheep? - Dick, Philip K. (Nxb. Đồng Nai, 2009)
San Francisco lies under a cloud of radioactive dust. People live in half-deserted apartment buildings, and keep electric animals as pets because so many real animals have died. Most people emigrate to Mars - unless they have a job to do on Earth. Like Rick Deckard - android killer for the police and owner of an electric sheep. This week he has to find, identify, and kill six androids which have escaped from Mars. They're machines, but they look and sound and think like humans - clever, dangerous humans. They will be hard to kill. The film Blade Runner was based on this famous novel.